CAPITAL BUDGETING FOR REPLACEMENT PROJECT EVALUATION (Study at PG Krebet Baru Bululawang Malang) - Aning Sri Rahayu (Jurnal Administrasi Bisnis, 2014)
The objective of this research is to evaluate the feasibility of long-term investment related to asset replacement project in PG Krebet Baru used capital budgeting techniques include payback period, accounting rate of return, net present value (NPV), benefit cost ratio (B/C ratio) and internal rate of return (IRR). Type of research is descriptive research with the case study method. Payback period method is equal to 14,93 years, it is faster compared to the useful life of assets that reach 20 years old. Accounting rate of return generate value 0,86 which is higher than value of ROE 2012 that equal to 0,75. Net present value obtained positive results equal to 733.121.448,90 with discount factor counted to17.17%. The B/C ratio is 1,05 times, IRR equal to 17,55%, it is greater than the cost of capital counted to 17.17 %. Based on these five methods, it can be concluded that the replacement project is feasible to be implemented by PG Krebet Baru. Key words: Replacement project, capital budgeting, payback period, accounting rate of return (ARR), net present value (NPV), benefit cost ratio (B/C ratio), internal rate of return (IRR)AbstrakPenelitian ini bertujuan untuk mengevaluasi kelayakan investasi jangka panjang dalam bentuk penggantian aset di PG Krebet Baru  dengan menggunakan teknik capital budgeting meliputi payback period, accounting rate of return (ARR), net present value (NPV), benefit cost ratio (B/C ratio) dan internal rate of return (IRR). Penelitian ini adalah penelitian deskriptif dengan menggunakan metode studi kasus. Metode payback period proyek penggantian aktiva akan terjadi setelah proyek berjalan selama 14,93 tahun, lebih cepat jika dibandingkan dengan usia ekonomis aset yang mencapai 20 tahun. Metode ARR menghasilkan nilai 0,86 dimana nilai ini lebih tinggi dibanding nilai ROE tahun 2012 senilai 0,75. Menggunakan metode NVP, investasi layak untuk dilakukan karena menghasilkan NPV positif senilai Rp 733.121.448,90 pada discount factor 17.17%. Metode B/C ratio menunjukkan proyek bernilai 1,05 kali, sedangkan IRR proyek 17,55%, lebih besar dari cost of capital proyek senilai 17.17 %. Berdasar lima metode tersebut, maka dapat disimpilkan bahwa proyek penggantian aset tersebut layak untuk dijalankan oleh PG Krebet Baru Kata kunci: Proyek penggantian, capital budgeting, payback period, accounting rate of return (ARR), net present value (NPV), benefit cost ratio (B/C ratio), internal rate of return (IRR)